Tinjauan Yuridis Restorative Justice Perkara Pidana Berdasarkan Peraturan Kejaksaan Nomor 15 Tahun 2000 - Diah Ayu Ma’rifatul Jannah (Jurnal Ilmiah Advokasi, 2025)
The application of restorative justice in criminal cases at the prosecutor's office level is one of the efforts to reform law enforcement that is oriented towards restoring justice for perpetrators and victims. This approach was introduced normatively through Attorney General Regulation Number 15 of 2020 as the legal basis for the implementation of restorative justice within the prosecutor's office. This study aims to analyze the concept and implementation of restorative justice in the handling of criminal cases at the prosecutor's office level and to assess the extent to which its application has fulfilled the principle of legal certainty. The research method used is normative juridical with a legislative and conceptual approach, through a review of regulations, doctrines, and the concept of restorative justice. The results of the study show that restorative justice functions as a win-win solution for perpetrators and victims by focusing on peaceful resolution without coercion and the restoration of social relations. However, the effectiveness of its application is highly dependent on the policies and discretion of law enforcement officials, particularly prosecutors, as well as the clarity of the criteria and implementation mechanisms regulated in the Attorney General's Regulation. This study concludes that the application of restorative justice at the prosecutor's office level has great potential in realizing substantive justice, but still requires strengthening of regulations and consistency in implementation to be in line with the principle of legal certainty. Keywords: restorative justice; criminal cases; prosecutor's office; legal certainty